(untitled) (Journal of Medicine, 2012)
The aim of the study was to investigate familial trend and socioeconomic status of the hypertensive patients attending at the Hypertension Clinic of Dhaka Medical College Hospital, Dhaka. The study period was from July 2009 to June 2010. A total of 417 patients were recruited of which 245 were male and 172 female respectively, and selected consecutively on the basis of defined criteria. The research instrument was an interviewer-administered questionnaire. For assessment of familial trend of hypertension, first and second degree relatives of the respondents were investigated. Results showed that majority of the respondents were educated of which 22.1%(n=92), 18.2%(n=76), 19.9%(83) and 13.7%(n=57) were secondary, higher secondary, graduate and postgraduate educated respectively. In profession, 64.4%(n=111) female had household works, and 56.8%(n=139) male were in service and 41.2%(n=101) businessmen and had monthly income of Tk. 10,000 to 80,000. The mean age of them was 47.4±6.9 years and BMI was 25.5±3.0 kg/m2. The nutritional status of them were normal in 40.5%(n=169) and rest had different degree of malnutrition. In malnutrition, 53.1%(n=130) male were overweight, 2.9%(n=7) obese and 0.8%(n=2) undernourished; and 51.2%(n=88) female were overweight, 11.0(n=19) obese and 1.2%(n=2) undernourished respectively. About 70.5%(n=294) of the studied hypertensive patients had positive history of hypertension in first and second degree relatives of which 17.3%(n=72) had single member positive history of hypertension, 18.2%(n=76) two, 16.8%(n=70) three, 14.1%(n=69) four and 4.1%(n=17) five members. In single member positive, most of them were in first degree relatives; in two members, 67.1%(n=51) were in first degree relatives and 27.6%(n=21) in both first and 2nd degree relatives; in three members, 64.3%(n=45) were in 1st degree and 31.4%(n=22) in both 1st and 2nd degree; in four members, 31.9%(n=22) were in 1st degree relationship, 17.4%(n=12) in 2nd degree and 50.7%(n=35) in both 1st and 2nd degree; and in five members, 17.6%(n=3) and 82.4%(n=14) in second degree, and both 1st and 2nd degree relatives respectively. Heath education and behavioral change intervention programs among the hypertensive population may be one of the most important applicable ways to control and/or prevention of hypertension and its complications in Bangladesh. DOI: http://dx.doi.org/10.3329/jom.v13i1.5941 JOM 2012; 13(1): 10-15